2022
DOI: 10.26444/aaem/152838
|View full text |Cite
|
Sign up to set email alerts
|

Viral, bacterial, and fungal contamination of Automated Teller Machines (ATMs)

Abstract: Introduction andObjective. While the qualitative information about bacterial and fungal pollution of automated teller machine (ATM) surfaces is available in the scientific literature, there are practically no studies precisely quantifying this type of contamination. Regarding viruses, such data in relation to ATM surfaces are not available at all. Materials and method. The quantitative and qualitative control of adeno-and coronaviruses, including SARS-CoV-2 (based on qPCR/RT-qPCR and v-qPCR/v-RT-qPCR), bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In the hygienic assessment of poultry house workplaces and outdoor air surrounding the studied poultry farm, the elaborated TLVs, based on volumetric sampling methods proposed by the Expert Group on Biological Agents at the Polish Interdepartmental Commission for Maximum Admissible Concentrations and Intensities for Agents Harmful to Health in the Working Environment, was used (Tab. 1) [52,53]. Comparison of bioaerosol concentrations with these hygienic standards showed that bacterial (including mesophilic and Gram-negative species) and fungal levels in the air measured at certain points in the production cycle (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…In the hygienic assessment of poultry house workplaces and outdoor air surrounding the studied poultry farm, the elaborated TLVs, based on volumetric sampling methods proposed by the Expert Group on Biological Agents at the Polish Interdepartmental Commission for Maximum Admissible Concentrations and Intensities for Agents Harmful to Health in the Working Environment, was used (Tab. 1) [52,53]. Comparison of bioaerosol concentrations with these hygienic standards showed that bacterial (including mesophilic and Gram-negative species) and fungal levels in the air measured at certain points in the production cycle (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Among the bacteria, the following species were identified: Micrococcus luteus, Micrococcus roseus, Staphylococcus capitis, Staphylococcus auricularis, Staphylococcus hominis, Staphylococcus haemolyticus, Staphylococcus warneri, Arthrobacter crystallopoietes, Arthrobacter woluwensis, Bacillus cereus, Bacillus firmus, Microbacterium liguefaciens, Pseudomonas lundensis, as well as actinomycetes of the genera: Actinomyces, Nocardia, Rhodococcus, and Streptomyces. Thus, it should be considered that typical air microflora were found in the studied samples [62,63].…”
Section: Dust Concentration Analysis and Microbiological Analysis Of ...mentioning
confidence: 99%
“…Material factors include hydroscopy, smoothness, roughness, composition, etc. [ 44 , 49 , 55 ]. Lee et al [ 5 ] studied the release of different fungal particles from different flood-damaged building materials in vitro: linoleum, rugs, carpets and pillows.…”
Section: Aerosolization Of Moulds Particles From Contamination Materialsmentioning
confidence: 99%